RESPON PEMERINTAH INDIA PASCA TRAGEDI MUMBAI ATTACKS TAHUN 2008 - Alchesar, Fernando Christian; Nugraha, A.A Bagus Surya Widya; Resen, Putu Titah Kawitri (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL); Vol 3 No 1 (2023): JURNAL DIKSHI, 2023)
This research  aims to describe India’s response to Mumbai Attacks 2008. India’s lack of preparedness and inconsistency in counter-terrorism policy allows a series of terrorist attacks spread across the nation. Until the brink of the most famous terrorist attack in India : Mumbai Attacks 2008, national security instruments were rapidly enhanced. It appears that the terrorist is outscoring India’s internal defense including MARCOS, NSG, and police department resulting in 4 days siege with a number of casualties. This research uses a descriptive qualitative method with data processed through a literature study. There are two conceptual frameworks applied in this research; the national security strategy concept and the risk management concept. Researchers expect this paper can deliver a comprehensive description of how India coping with terrorism by utilizing risk management